DETERMINATION OF BAHDINI DIALECT SPEAKERS’ PERCEPTION IN ZAKHO CITY - Younis, Hala; Salih, Salwa (Humanities Journal of University of Zakho, 2026)
This study presents an investigation into the perceptual dialectology and speakers’ attitudes of Zakho Bahdini dialect speakers concerning various Bahdini dialect variations within Duhok province. The primary objective was to ascertain the degree of awareness and attention paid by individuals to language and dialect differences within their linguistic landscape. A quantitative research design was employed, involving 50 participants who are citizens of Zakho and native Bahdini dialect speakers. Data were collected via a structured survey utilizing three distinct Duhok maps as stimuli. Participants rated dialect variations based on three criteria: Dialect Difference (on a 1-4 scale), Social Prestige (on a 1-7 scale), and Degree of Preference (on a 1-7 scale). The collected data were subsequently analyzed using the Statistical Package for the Social Sciences (SPSS). Analysis revealed a significant perceived difference between Zakho and Kalak dialects regarding Dialect Differences, a perception attributed to geographical distance, cultural, and tribal distinctions. Furthermore, Zakho citizens demonstrated the lowest social prestige for the Shekhan dialect. Conversely, Semel and Akree dialects were identified as the first and second most preferred, respectively, concerning the Degree of Preference.